A Regulatory Framework on Foreign Direct Investment as a Factor in Determining the Economic Growth in Malaysia Post-Covid-19 Pandemic - Keita, Kain; Razak, Aida Binti Abdul; Abdullah, Nor Anita (NAJAHA, 2023)
A country's economic growth rate is the percentage change in the value of all goods and services produced during a certain period compared to the previous period. Since the Covid-19 pandemic was announced and hurting all businesses, several companies have depended on foreign direct investment (FDI) investment. Hence, this study aims to pinpoint new trends that Malaysian legal investment decision makers should follow to prepare for FDI attractiveness post-Covid-19. This study applies empirical theoretical methods with a qualitative approach to the relationship between state governments and foreign direct investors. The results of the analysis show that many countries that offer FDI face economic deficits and are more willing to develop themselves than others. It was agreed that FDI had a positive impact on Malaysia's economic growth and this growth was faced with shortcuts due to the negative impact of the Covid-19 pandemic. In addition, Malaysia has long-standing political problems which have impacted the country's FDI attractiveness. His contribution is to help these components adopt laws and regulations that are good for the future as the country has been dramatically impacted economically.